Macro- and megafauna recorded in the submarine Bari Canyon (southern Adriatic, Mediterranean Sea) using different tools - D’ONGHIA, G.; CAPEZZUTO, F.; CARDONE, F.; CARLUCCI, R.; CARLUCCIO, A.; CHIMIENTI, G.; CORRIERO, G.; LONGO, C.; MAIORANO, P.; MASTROTOTARO, F.; PANETTA, P.; ROSSO, A.; et al. (Mediterranean Marine Science, 2015)
Macro- and megafauna were recorded in the submarine Bari Canyon (southern Adriatic Sea, Mediterranean Sea) during an oceanographic cruise carried out in May-June 2012 and an experimental fishing survey conducted in November 2013. During the former, a total of 20 benthic samples were taken using a Van Veen grab at depths between 268 and 770 m and 4 deployments of a baited lander, for about 43 hours of video records, were carried out at depths between 443 and 788 m. During the latter, 8 longline fishing operations were conducted from 338 down to 612 m. Eighty-five living benthic and benthopelagic species were recorded: 29 Porifera, 1 Cnidaria, 2 Mollusca, 11 Annelida, 1 Arthropoda, 19 Bryozoa, 3 Echinodermata and 19 Chordata. A total of 51 species are new records for the Bari Canyon, 29 new records for the Adriatic Sea. Among the Porifera Cerbaris curvispiculifer is a new addition for the Italian Sponge Fauna. The first certain record of living specimens for the bryozoan Crisia tenella longinodata is reported. A total of 6 Mediterranean endemic species have been identified: 4 Porifera and 2 Annelida. The bathymetric range of some species has been extended. New information acquired for deep sea species confirms their importance in the structure of cold-water coral communities. This study has updated the knowledge on the biodiversity of the Adriatic Sea, as well as of the Bari Canyon in particular, one of the sites designated as “jewels of the Mediterranean” for which urgent conservation measures are needed.